Finding Creativity in an Artificial Artist. (4th June 2013) - Norton, David; Heath, Derrall; Ventura, Dan
Abstract Creativity is an important component of human intelligence, and imbuing artificially intelligent systems with creativity is an interesting challenge. In particular, it is difficult to quantify (or even qualify) creativity. Recently, it has been suggested that conditions for attributing creativity to a system include: appreciation, imagination, and skill. We demonstrate and describe an original computer system (called DARCI) that is designed to produce images through creative means. We present methods for evaluating DARCI and other artificially creative systems with respect to appreciation, imagination, and skill, and use these methods to show that DARCI is arguably a creative system.